Embracing the Evolution of Pharmacy Practice by Empowering Pharmacy Technicians - Ryan Burke (Pharmacy, 2020)
While pharmacy technician roles in some practice settings are expanding beyond the traditional dispensing activities to include advanced or specialized tasks such as immunization administration, medication history collection, and final product verification, these practices are not yet widespread. There are apparent barriers to expanding the role of pharmacy technicians, including inconsistency in the education, training, and certification requirements across the United States, and regulations that have not kept pace with the evolving role of pharmacy technicians. Every corner of the profession has an opportunity, and responsibility, to elevate pharmacy technicians in an effort to advance safety and better serve patients. Regulators can expand the responsibilities that may be delegated to technicians, professional organizations can bring pharmacy technicians into the fold, employers can build career ladders to allow for advancement, and individual pharmacists and pharmacy technicians can advocate and engage.